Análisis del efecto de la afiliación al Seguro Integral de Salud en el gasto de bolsillo en salud realizado por adultos mayores pobres con enfermedades crónicas en Perú: Un análisis del 2009 - 2019 mediante una variable instrumental - Bazan López, Iveth Zarita (2024)
This project focuses on optimizing customer service processes at the Municipal Government of Marañon by implementing a bilingual (Spanish-Quechua) chatbot developed with artificial intelligence. The language barrier in assisting Quechua-speaking citizens and the administrative staff’s workload have created the need for this technological solution, aimed at improving service efficiency and quality. The chatbot, developed using an agile methodology, will allow citizens to access information about documentary procedures immediately and in their native language. Expected outcomes include reduced response times, reduced workload for staff, and improved citizen satisfaction. The implementation relies on Dialogflow for natural language processing and Facebook Messenger as the interaction platform. Furthermore, project management will follow the PMBOK guidelines, ensuring efficient resource management, scheduling, and quality control throughout the project's lifecycle.